Implementasi Konsep Eudamonia dalam Perancangan Interior Elderly Community Center di Surabaya - Mellisa Lani Sugiharto; Diana Thamrin; lucky basuki (Intra, 2018)
Along with the large number of population in the city of Surabaya, this city is also the second busiest city in Indonesia with many activities outside of their residence. yang kurang diperhatikan oleh anggota keluarganya. Padahal diumur yang tidak lagi muda, lansia memiliki kebutuhan yang khusus untuk memelihara kesehatan fisik dan psikis mereka. This will raise the number of elders being left behind by their family members. In fact, on their senior year the elderlies have special necessities to maintain their physical and psychological health. The design purpose is to accommodate the elderly to do activities during public work hours. The facility is designed to support users in fulfilling the physical, psychological, and social needs of the elderly. The design method that will be used is Standford Design Thinking Process in 2009, which consists of understand, observe, ideate, prototype, test, and implementation. The results of the design is an Elderly Community Center with the concept of Eudamonia, which means the circumstances in which human become happy, healthy, and prosperous individuals. The facilities provided in this day care includes gym, physiotherapy, infrared therapy, area for Tai-chi and aerobic, reading area, etc.